Effect of Welding Heat Input on the Microstructure and Impact Toughness of HAZ in 420 MPa-Grade Offshore Engineering Steel - Liu, Dekun; Yang, Jian; Zhang, Yinhui; Qiu, Yunlong; Cheng, Guoguang; Yao, Meiyi; Dong, Jianxin (Frontiers in Materials, 2021)
In the present work, the effect of the welding heat input on the microstructure, martensite-austenite (M-A) constituents and impact toughness of the coarse-grained heat-affected zone (CGHAZ) in offshore engineering steel with Ca deoxidation is studied. With the heat input increased from 50 to 100 kJ/cm, the HAZ toughness is decreased rapidly, while the measured micro-hardness decreases steadily as the heat input is increased from 50 to 200 kJ/cm. The grain sizes are increased from 52 to 132 μm, and the width of bainite lath from 0.4 to 2 μm. The area fraction of lath bainite (LB) is decreased, while the area fraction of granular bainite (GB) is increased. The average width of M-A constituents grows from 0.3 to 0.6 μm, and the average length from 0.5 to 0.9 μm. Its area fraction is increased from 5.3% to 8.6%, then decreased to 6.1%, and its number density is decreased from 0.7 to 0.2 μm-2. The morphologies of M-A constituents change from dot-like to slender and blocky, which are deleterious to impact toughness of HAZ. The fracture mechanism changes from ductile to quasi-cleavage and cleavage as the heat input is increased. As the M-A constituents are always found as the cleavage initiation, they should be responsible for the decrease in HAZ toughness when the heat input is above 100 kJ/cm.